Objective identification of multiple large fire climatologies: an application to a Mediterranean ecosystem - J Ruffault; V Moron; R M Trigo; T Curt (Environmental Research Letters, 2016)
There is growing evidence that the climatic conditions favorable to the occurrence of large fires (LFs) might not be unique within a homogeneous biogeographic area. But the identification of these coexistent multi-scalar climatologies often relies on empirical observations. Here we classify summer LFs (>120 ha) in Mediterranean France for the period 1973 to 2012, according to their local-scale weather conditions (i.e. temperature, relative humidity, wind speed and fuel moisture proxies). Three distinct climatologies were identified, and were referred as fire weather types (FWTs). (i) One of them is associated with near-normal atmospheric conditions. (ii) A heat-driven (HD) type is mostly discriminated by warm anomalies. (iii) A wind-driven (WD) type is mostly discriminated by faster winds, but cooler anomalies than usual. The frequency of WD and near-normal LFs sharply decreased in southern France over the last decades while the frequency of HD fires remained unchanged. In addition the current increase in HD potential fire days indicates a potential shift in the dominant FWT for this region. This approach offers a better understanding of the variations in fire activity and fire spread patterns in the context of contemporaneous global changes.